2015
DOI: 10.1007/s00404-015-3665-6
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical analyses and effects of Alchemilla mollis (Buser) Rothm. and Alchemilla persica Rothm. in rat endometriosis model

Abstract: The results of the present study revealed that the aerial part extracts of A. mollis and A. persica could be beneficial in the treatment of endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 44 publications
0
17
0
1
Order By: Relevance
“…Hyperoside and isoquercitrin which are the major components of the aerial parts of the both species were quantified as 0.2 ± 0.002 mg and 0.6 ± 0.003 mg, respectively A. Mollis; and 0.2 ± 0.001 mg and 0.5 ± 0.001 mg respectively in A. persica for 100 mg plant material. In consequence, the phytochemical profiles of A. mollis and A. persica were found to be similar in terms of their HPLC chromatograms (Kupeli Akkol et al, 2015).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Hyperoside and isoquercitrin which are the major components of the aerial parts of the both species were quantified as 0.2 ± 0.002 mg and 0.6 ± 0.003 mg, respectively A. Mollis; and 0.2 ± 0.001 mg and 0.5 ± 0.001 mg respectively in A. persica for 100 mg plant material. In consequence, the phytochemical profiles of A. mollis and A. persica were found to be similar in terms of their HPLC chromatograms (Kupeli Akkol et al, 2015).…”
Section: Discussionmentioning
confidence: 72%
“…In the present study, wound healing activity of A. mollis and A. persica, both of which have quite similar phytochemical profile according to our previous research (Kupeli Akkol et al, 2015), were selected in order to be evaluated by using in vivo wound models. The extracts prepared from the aerial parts of A. mollis and A. persica displayed significant wound healing effect with regard to the contraction and tensile strength values, as well as histopathological and hydroxyproline analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species of Alchemilla have been reported for the treatment of dysmenorrhea, gastrointestinal disorders, inflammation of the mouth and throat, eczema and skin rashes (Kupeli Akkol et al, 2015). Alchemilla mollis is traditionally used for the treatment of wounds and excessive menstruation (Makau et al, 2013;Trendafilova et al, 2011;Yarnel and Abascal, 2009).…”
Section: Alchemilla Mollis and Alchemilla Persicamentioning
confidence: 99%
“…4 The first line of treatment of endometriosis is hormonal regulation along with the use of oral contraceptives for regulating the menstrual cycle, for ensuring long-term safety. 8 Likewise, numerous in vitro and in vivo studies have demonstrated the potential of certain phytochemicals to act as therapeutic adjuvants for the treatment of endometriosis. 5 Therefore, the only effective treatment for endometriosis is surgery, even though the rate of recurrence is 30% within 4 years.…”
Section: Introductionmentioning
confidence: 99%